PERAN HUKUM NASIONAL ATAS KEPEMILIKAN TERHADAP ASET DIGITAL NON – FUNGIBLE TOKEN (NFT) - Samuel M.P. Hutabarat (Gloria Justitia, 2023)
In the world of Metaverse, assets or objects that are almost the same as those in the real world are introduced. Non-Fungible Token or what is often referred to as NFT which is a digital token that is linked to the large Blockchain system, which can be traded. As an object that can be traded, it is necessary to pay close attention to the material nature of the NFT from the perspective of civil law. This is useful for determining the process of transferring ownership of the NFT itself. On the other hand, not all countries already have provisions governing digital assets. The Unidroit Principles on Digital Assets and Private Law provide guidelines for regulating ownership of digital assets from a civil law perspective.